y - 1 = ⁵/₆(x - 4)
y - 1 = ⁵/₆(x) - ⁵/₆(4)
y - 1 = ⁵/₆x - 3¹/₃
+ 1 + 1
y = ⁵/₆x - 2¹/₃
⁻⁵/₆x + y = ⁵/₆x - ⁵/₆x - 2¹/₃
-6(⁻⁵/₆x + y) = -6(-2¹/₃)
-6(⁻⁵/₆x) - 6(y) = 14
5x - 6y = 14
The commutative property of 9+8=17 is 8+9=17 because the commutative property states that it doesn't matter the order of the number but as long as u get the same answer.
Answer:
for the first one I think it is -5/-2 second is 1/-4 third one is 2/1 this may not be correct
Step-by-step explanation:
Mean:
E[Y] = E[3X₁ + X₂]
E[Y] = 3 E[X₁] + E[X₂]
E[Y] = 3µ + µ
E[Y] = 4µ
Variance:
Var[Y] = Var[3X₁ + X₂]
Var[Y] = 3² Var[X₁] + 2 Covar[X₁, X₂] + 1² Var[X₂]
(the covariance is 0 since X₁ and X₂ are independent)
Var[Y] = 9 Var[X₁] + Var[X₂]
Var[Y] = 9σ² + σ²
Var[Y] = 10σ²